Pharmaceutical Characterization and In Vivo Evaluation of Orlistat Formulations Prepared by the Supercritical Melt-Adsorption Method Using Carbon Dioxide: Effects of Mesoporous Silica Type - Heejun Park; Kwang-Ho Cha; Seung Hyeon Hong; Sharif Md Abuzar; Seungyeol Lee; Eun-Sol Ha; Jeong-Soo Kim; In-Hwan Baek; Min-Soo Kim; Sung-Joo Hwang (MDPI AG, 2020)
Orlistat, an anti-obesity drug, has two critical issues-the first is its low efficacy due to low water solubility and the second is side effects such as oily spotting due to its lipase inhibition. The present study was designed to propose a solution using a formulation with mesoporous silica to simultaneously overcome two issues. Orlistat was loaded onto mesoporous silica by the supercritical melt-adsorption (SCMA) method, using carbon dioxide (CO2). Various types of mesoporous silica were used as adsorbents, and the effects of the pore volume, diameter and particle size of mesoporous silica on the pharmaceutical characteristics were evaluated by various solid-state characterization methods and in vitro and in vivo studies in relation to pharmacological efficacy and the improvement of side effects. The results showed that the pore volume and diameter determine loadable drug amount inside pores and crystallinity. The dissolution was significantly influenced by crystallinity, pore diameter and particle size, and the inhibition of lipase activity was in proportion to the dissolution rate. In vivo studies revealed that the serum triglyceride (TG) concentration was significantly decreased in the group administered amorphous orlistat-loaded Neuisilin®UFL2 with the highest in vitro dissolution rate and lipase activity inhibition in comparison to the commercial product. Furthermore, oily spotting tests in rats revealed that undigested oil was adsorbed onto mesoporous silica after orlistat was released in the gastro-intestinal tract, and it correlated with in vitro result that oil adsorption capacity was dependent on the surface area of empty mesoporous silica. Therefore, it was concluded that mesoporous silica type plays a major role in determining the pharmaceutical characteristics of orlistat formulation prepared using SCMA with CO2 for improving the low solubility and overcoming the side effects.